The Giant Postman - Sally Grindley (London, United Kingdom Pan MacMillan, 2000)
The Giant Postman is scaring everyone in the village until Billy comes up with a brilliant idea. He writes a letter to the Giant who has never had a letter before. The Giant replies saying sorry, but giants can't help being clumsy.
Keywords: Read Aloud -- Read Aloud